ANALYSIS OF TRAVEL CAREER PATTERNS IN TOURISM DESIGN AREA AT SUNSET BEACH KARANGPAPAK - Shahnaz Keke Rahmani; Ida Ayu Sawitri Dian Mawarni; Rachmat Taufick Hardi (KURVATEK, 2022)
Karangpapak Sunset Beach is one of the beaches in Sukabumi Regency which has tourism potential to be visited by tourists because it has advantages and interesting characteristics, namely to learn to surf. In addition, travel career patterns are also influential in developing a tourist area. However, with the many tourist motives of tourists and the limited attractiveness they have and areas that are not equipped with tourism elements, it is necessary to analyze travel career patterns to determine what tourist areas are needed by tourists and by referring to the elements of tourism planning. The method used is a qualitative method by conducting participatory observations, interviews, documentation and literature review. The results of the analysis explain that there is a tendency that tourists on Sunset Beach Karangpapak have reached the middle layer motives and outer layer motives where it can be said that tourists will revisit Sunset Beach Karangpapak. This analysis was carried out as a result of a comprehensive spatial study.